2021
DOI: 10.4102/phcfm.v13i1.2691
|View full text |Cite
|
Sign up to set email alerts
|

Scorecard metrics for assessing the extent of integration of community health worker programmes into national health systems

Abstract: Background: The effectiveness of community health workers (CHWs) in delivering community-based preventive services is often curtailed by inadequate or complete lack of integration of the CHW programmes into national health systems. Although literature has defined the context and guidelines for integrating CHW programmes into health systems, indicators to quantitatively assess the extent of integration are inadequately addressed.Aim: This article presents an integration scale – CHW Programme Integration Scoreca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 31 publications
(54 reference statements)
0
7
0
Order By: Relevance
“…34 For the purpose of this study, the integration parameters and indicators for WHO's human resources for health building block and CHW's recruitment, education and certification program component were extracted from the scorecard. 34 Scoring based on the CHWP-ISM scale was done according to the criteria as presented below. A "Yes"/tick was assigned if evidence for the occurrence/presence/execution of any of the stated indicators were presented and/or corroborated through the three means data were collected.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…34 For the purpose of this study, the integration parameters and indicators for WHO's human resources for health building block and CHW's recruitment, education and certification program component were extracted from the scorecard. 34 Scoring based on the CHWP-ISM scale was done according to the criteria as presented below. A "Yes"/tick was assigned if evidence for the occurrence/presence/execution of any of the stated indicators were presented and/or corroborated through the three means data were collected.…”
Section: Discussionmentioning
confidence: 99%
“…34 For the purpose of this study, the integration parameters and indicators for WHO’s human resources for health building block and CHW’s recruitment, education and certification program component were extracted from the scorecard. 34…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study was based on the earlier reported study (38), which is part of a wider study undertaken to generate items suitable for assessing the extent of integration of CHW programs into national HS. The study (Mupara et al (38) study on integration indicators) was based on WHO's building blocks for strengthening health systems (HSs) (Figure 1).…”
Section: Methodology Theoretical Considerations Item Selection and St...mentioning
confidence: 99%
“…This study validated newly developed scorecard metrics for measuring the extent of CHW programs' integration into national health systems (CHWP-ISM) in Sub-Saharan Africa (38) at the policy level. The paper tests the proposed CHW integration metrics scale's construct validity, dimensionality, and reliability.…”
Section: Introductionmentioning
confidence: 96%